Esophagogastric junction distensibility in hiatus hernia. Issue 5 (19th March 2015) - Lottrup, C.; McMahon, B. P.; Ejstrud, P.; Ostapiuk, M. A.; Funch‐Jensen, P.; Drewes, A. M.
Summary: Hiatus hernia is known to be an important risk factor for developing gastroesophageal reflux disease. We aimed to use the endoscopic functional lumen imaging probe (EndoFLIP) to evaluate the functional properties of the esophagogastric junction. EndoFLIP assessments were made in 30 patients with hiatus hernia and Barrett's esophagus, and in 14 healthy controls. The EndoFLIP was placed straddling the esophagogastric junction and the bag distended stepwise to 50 mL. Cross‐sectional areas of the bag and intra‐bag pressures were recorded continuously. Measurements were made in the separate sphincter components and hiatus hernia cavity. EndoFLIP measured functional aspects such as sphincter distensibility and pressure of all esophagogastric junction components and visualized all hiatus hernia present at endoscopy. The lower esophageal sphincter in hiatus hernia patients had a lower pressure (e.g. 47.7 ± 13.0 vs. 61.4 ± 19.2 mm Hg at 50‐mL distension volume) and was more distensible ( all P < 0.001) than the common esophagogastric junction in controls. In hiatus hernia patients, the crural diaphragm had a lower pressure (e.g. 29.6 ± 10.1 vs. 47.7 ± 13.0 mm Hg at 50‐mL distension volume) and was more distensible ( all P < 0.001) than the lower esophageal sphincter. There was a significant association between symptom scores in patients and EndoFLIP assessment. Conclusively, EndoFLIP was a useful tool. To evaluate the presence of a hiatus hernia and to measure the functional properties of the esophagogastric junction. Furthermore, EndoFLIP distinguished the separate esophagogastric junction components in hiatus hernia patients, and may help us understand the biomechanics of the esophagogastric junction and the mechanisms behind hiatal herniation.